Who is Being Served? How Competing Norms and Values Shape the Transitional Justice Agenda in Zimbabwe. (2nd January 2022) - Matshaka, Chenai; Wielenga, Cori
ABSTRACT: Any transitional justice process involves a multiplicity of actors and competing norms and values that shape the transitional justice agenda. This article is concerned with the ways competing norms and values have shaped the transitional justice agenda in Zimbabwe. It makes the argument that the privileging of a neoliberalist perspective, as well as a human rights discourse in dealing with the concerns of post-conflict societies, has posed challenges for meaningful transitional justice interventions in Zimbabwe and on the African continent and suggests a nuanced approach to transitional justice that captures the history, culture and other dynamics that shape a country's politics. This article draws from interviews with four civil society activists and scholars on transitional justice in Zimbabwe, as well as narratives are drawn from a categorical content analysis of the reports and other publications of four civil society organisations – Zimbabwe Human Rights NGO Forum (ZHRNGOF), Zimbabwe Peace Project (ZPP), Amnesty International (Zimbabwe) and Zimbabwe Human Rights Association (ZIMRIGHTS). The civil society organisations and activists were purposively sampled based on the work they have done in the area under study, as well as their understanding of the context and its nuanced complexities.